2018
DOI: 10.2298/ntrp1801100m
|View full text |Cite
|
Sign up to set email alerts
|

Organ doses and associated cancer risks for computed tomography examinations of the thoracic region

Abstract: The use of com puted to mog ra phy is in creas ing rap idly and doses are not neg li gi ble es pe cially when med i cal pro ce dures re quire more than one scan. The pur pose of the pres ent study was to mea sure doses in an an thro po mor phic Rando phan tom dur ing a stan dard and low dose com puted to mog ra phy pro to col of the tho rax and to es ti mate risks of ra di a tion in duced cancer for adult pa tients that un dergo mul ti ple com puted to mog ra phy scans of the tho rax. Thermoluminescent and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A total of 44,657 relevant studies were preliminarily reviewed. In total, 125 studies satisfied the eligibility criteria for full-text screening and 25 were eventually included for this meta-analysis [2,[8][9][10][11][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Of these 25 studies, 5 reported actual cancer cases [8,10,11,35,36], 19 estimated cancer cases by calculating LAR [2, 9, 37-53], 1 reported expected cancer cases in control group [54], and all were published since 2007.…”
Section: Hallmarks Of Included Studiesmentioning
confidence: 99%
“…A total of 44,657 relevant studies were preliminarily reviewed. In total, 125 studies satisfied the eligibility criteria for full-text screening and 25 were eventually included for this meta-analysis [2,[8][9][10][11][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Of these 25 studies, 5 reported actual cancer cases [8,10,11,35,36], 19 estimated cancer cases by calculating LAR [2, 9, 37-53], 1 reported expected cancer cases in control group [54], and all were published since 2007.…”
Section: Hallmarks Of Included Studiesmentioning
confidence: 99%
“…An an thro po mor phic her maph ro dite phan tom [15] RS-113T that has an at ten u a tion co ef fi cient of a pa tient with a body mass of 74 kg and a height of 175 cm (Ra di ol ogy sup port de vices, 2009) was used in the first phase. Twenty im ages were per formed al together, ten on each unit.…”
Section: Phan Tom Mea Sure Mentsmentioning
confidence: 99%
“…Currently, the most used imaging techniques to detect cancer are based on X-ray sources (e.g., computed tomography scan), high magnetic fields (e.g., magnetic resonance imaging), or radioactive substances as tracers (e.g., positron emission tomography scan); however, these techniques can cause side effects in the patients. In fact, to improve the contrast in the images sometimes several scans are required, increasing the chances to suffer side effects [ 4 , 5 , 6 , 7 , 8 , 9 ]. In the last decade an alternative complementary detection technique, “fluorescence microscopy”, is in expansion since it is less invasive and offers a safe detection with high sensitivity, specificity, and resolution.…”
Section: Introductionmentioning
confidence: 99%